1998
DOI: 10.1152/ajpheart.1998.274.4.h1106
|View full text |Cite
|
Sign up to set email alerts
|

KATP channels are common mediators of ischemic and calcium preconditioning in rabbits

Abstract: Calcium preconditioning (CPC), like ischemic preconditioning (IPC), reduces myocardial infarct size in dogs and rats. ATP-sensitive potassium (KATP) channels induce cardioprotection of IPC in these animals. To determine whether KATP channels mediate both IPC and CPC, pentobarbital sodium-anesthetized rabbits received 30 min of coronary artery occlusion followed by 180 min of reperfusion. IPC was elicited by 5 min of occlusion and 10 min of reperfusion, and CPC was elicited by two cycles of 5 min of calcium inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
1
19
1
Order By: Relevance
“…In fact, this is the case. Calcium preconditioning has been well known for a decade (12,19,21); considerable literature supports the concept that ␣ 1 -receptor stimulation is cardioprotective (1,2,28), and preliminary studies have shown ouabain to be cardioprotective (22). Moreover, each of these modes of protection has been shown to involve K ATP channels.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this is the case. Calcium preconditioning has been well known for a decade (12,19,21); considerable literature supports the concept that ␣ 1 -receptor stimulation is cardioprotective (1,2,28), and preliminary studies have shown ouabain to be cardioprotective (22). Moreover, each of these modes of protection has been shown to involve K ATP channels.…”
Section: Discussionmentioning
confidence: 99%
“…Also, giving a K ATP antagonist with a volatile anesthetic reduced the preconditioning effects despite a similar temporary depression of function in both groups (24). On the other hand, a temporary increase in extracellular calcium, which induces a positive inotropic effect, has been shown to precondition hearts (26). In contrast, brief exposure to a volatile anesthetic decreased intracellular Ca 2ϩ transients (35).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there has been considerable speculation that I K ATP may play a cardioprotective role in various preconditioning and I/R settings (6,10,21,27,38,44). Interestingly, perhaps depending on the experimental setting, both I K ATP activation (6, 28) and I K ATP attenuation (19,36,47) have been associated with cardioprotection and/or improved recovery after I/R challenge.…”
mentioning
confidence: 99%